Distributed Video Coding with Shared Encoder/Decoder Complexity - Clerckx, Tom; Munteanu, Adrian; Cornelis, Jan; Schelkens, Peter (2007 IEEE International Conference on Image Processing, 2007)
Distributed video coding is a coding paradigm that allows complexity to be shared between encoder and decoder. In this context, video coding systems have been developed with encoder complexities similar to H.263+ intra-coding, while obtaining compression performance comparable to H.263+ inter coding. The decoders in these systems typically employ motion-compensated frame interpolation or extrapolation to generate side-information. However, as motion complexity of the video sequence increases, such generators fail to provide reliable side information. This paper proposes a pixel-domain distributed video coding method, combining low-complexity encoder-side bitplane motion estimation with decoder-side motion-compensated frame interpolation. It is shown that such a system is more suitable for sequences with increased motion complexity, compared to codecs that employ motion estimation at the decoder only.